Demographic and Attitudinal Factors of Adherence to Quarantine Guidelines During COVID-19: The Italian Model - Carlucci, Leonardo; D’Ambrosio, Ines; Balsamo, Michela (Frontiers in Psychology, 2020)
In Italy a large outbreak of coronavirus disease 2019 (COVID-19) occurred from 2020 January 30, before WHO has stated that it is a pandemic. The nationwide quarantine had the desired impact of controlling the epidemic, although had presented many challenges, given its large economic and social costs. Complete adherence to recommendations can potentially decelerate and reduce infectious disease outbreaks. To date, it is not clear how compliant the Italian public has been with voluntary home quarantine neither which factors have influenced an individual’s decision to comply with a quarantine order. The purposes of this study were to investigate the degree of the adherence with quarantine restrictions and the factors associated with the self-reported adherence. During the third week of the national lockdown, 3672 Italian quarantined adult residents (65% females, range: 18-85 years) participated in an online cross-sectional survey focused on the risk perception of contracting COVID-19 and their reported adherence with quarantine protocols. Analysis of variance showed significant differences among demographic groups in tendency to comply with quarantine orders, with women, most educated people, residents of Southern Italy, middle-aged individuals, and health workers more likely to adhere to quarantine guidelines. As well, participants exhibiting the perception, anxiety and susceptibility of risk of contracting COVID-19 disease were found significantly more likely to adhere to quarantine guidelines. The results of this study can help public health policy makers to recognize target populations for COVID-19 prevention and health education, and to understand how inform communication strategies aimed at minimizing the impact and spread of the disease.